Justice Involvement and Treatment Use Among Rural Veterans - Finlay, Andrea K. (Rural Ment Health, 2018)
Veterans in rural areas and veterans involved in the criminal justice system have experienced less access to, and use of, health care. However, there is limited information on the treatment needs and health care access of justice-involved veterans who live in rural areas. This study used national Veterans Health Administration data from fiscal year 2014 to examine the interactive effect of rural/urban residence and justice involvement on mental health and substance use disorder treatment entry among veterans diagnosed with mental health or substance use disorders. Of veterans residing in rural areas, 15,328 (2.5%) were justice-involved and 607,819 (97.5%) veterans had no known justice involvement. Among veterans in urban areas, 54,525 (4.3%) were justice-involved and 1,213,766 (95.7%) had no known justice involvement. Rural residence was associated with lower access to mental health or substance use disorder treatment in the non-justice-involved sample but not the justice-involved sample. Justice-involvement was associated with higher odds of entering mental health or substance use disorder treatment for veterans in rural and in urban areas. Substance use disorder treatment entry could be improved for all veterans, particularly rural veterans who are not justice-involved. Telehealth, outreach services, and integrated treatment may help address challenges to treatment entry experienced by rural veterans and justice-involved veterans.